Flow induced fluttering of a hinged vertical flat plate. (1st February 2015) - Fernandes, A.C.; Mirzaeisefat, S.
Abstract: This work addresses the behavior of fluttering motion in a hinged vertical flat plate allowed to rotate about its vertical axis, under the influence of uniform current. This problem has one degree of freedom and the study aims to understand the fluttering behavior. Fluttering (rotational oscillations) is a phenomenon that may occur when a leaf, a playing card, airplane debris or other more complex objects fall. It may also occur during the pendulous installation method of a large manifold (PIM) in an offshore deep water site. At first, the experimental study started with the static case. Afterward, the dimensional analysis, experiments and quasi-steady modeling devised a natural frequency for the fluttering motion. This frequency is linearly proportional to the incoming flow velocity and inversely proportional to the flat plate width. This response frequency of fluttering is due to a flow behavior that maybe systematized as a practically linear "hydrodynamic torsional spring" and the inertia considering the added mass. Highlights: This paper discusses the behavior a hinged vertical flat plate submitted to a uniform current. This is a very simple problem with 1-DOF but very complicated to explain. The paper demonstrates that the self oscillatory motion is surprisingly well behaved. According to experiments, a surprisingly linear moment coefficient for angles of attack from 0° to 75° shows up.